Rapid Health and Needs assessments after disasters: a systematic review - Yzermans CJ; van Bokhoven Irene; Korteweg Helena A; Grievink Linda (BMC, 2010)
Abstract Background Publichealth care providers, stakeholders and policy makers request a rapid insight into health status and needs of the affected population after disasters. To our knowledge, there is no standardized rapid assessment tool for European countries. The aim of this article is to describe existing tools used internationally and analyze them for the development of a workable rapid assessment. Methods A review was conducted, including original studies concerning a rapid health and/or needs assessment. The studies used were published between 1980 and 2009. The electronic databasesof Medline, Embase, SciSearch and Psychinfo were used. Results Thirty-three studies were included for this review. The majority of the studies was of US origin and in most cases related to natural disasters, especially concerning the weather. In eighteen studies an assessment was conducted using a structured questionnaire, eleven studies used registries and four used both methods. Questionnaires were primarily used to asses the health needs, while data records were used to assess the health status of disaster victims. Conclusions Methods most commonly used were face to face interviews and data extracted from existing registries. Ideally, a rapid assessment tool is needed which does not add to the burden of disaster victims. In this perspective, the use of existing medical registries in combination with a brief questionnaire in the aftermath of disasters is the most promising. Since there is an increasing need for such a tool this approach needs further examination.